Public Financial Accountability and Distributive Justice in International Space Exploration: A Normative Legal Analysis from Indonesia - Istianingsih; Sujono; Diding Rahmat (KRTHA BHAYANGKARA, 2026)
This study examines public financial accountability and distributive justice in international space exploration from a normative legal perspective. Despite the rapid expansion of space activities and the increasing allocation of public funds, international space law remains primarily focused on technical responsibility and liability, while lacking binding norms on fiscal transparency, public financial reporting, and accountability. This normative gap raises concerns regarding the equitable governance of outer space as a global common. Employing normative legal research, this study analyzes key international space law instruments, particularly the Outer Space Treaty (1967) and related conventions, together with Indonesia’s national legal framework under Law No. 21 of 2013 on Space Activities. Statutory, conceptual, and comparative approaches are used to assess the adequacy of existing legal norms. The findings reveal an international fiscal accountability gap that undermines the operationalization of the principle of the province of all mankind and contributes to structural inequality in space exploration. At the national level, Indonesia’s space law framework is largely declarative and insufficiently integrated with public finance regulation. This study concludes that normative reform is required to strengthen fiscal transparency, accountability, and distributive justice in space governance.